CORRELATION BETWEEN THE QUALITY INDICATORS OF BULL SEMEN LONG-TERM STORAGE - Ляшенко, А. О. (Scientific Progress & Innovations, 2015)
The investigation of the relationship between the physiological, morphological and morphometric characteristics of bulls’ sperm of different breeds of the Bank of genetic resources, depending on the storage term was carried out. We determine the correlation between indicators of sperm of morphology and morphological indexes. We determine the inverse relationship between the content of pathological forms and the number of normal acrosome: the greater number of sperm with normal acrosome, the less number of abnormal cells r= -0,3 (p<0,001). There is a negative correlation between the number of abnormal sperm and HOST (r= -0,54) (p<0,001), between the percentage of damaged acrosome, the number of abnormal cells, the number of pathological and dead cells and the length of the different parts of the sperm (r= -0,2) (p<0,05).